Gender differences in the relationship between socioeconomic status and height loss among the elderly in South Korea: Korean National Health and Nutrition Examination Survey 2008–2010. Issue 34 (August 2017) - Kim, Yang-Hyun; Ahn, Kyung-Sik; Cho, Kyung-Hwan; Kang, Chang Ho; Cho, Sung Bum; Han, Kyungdo; Rho, Yong-Kyun; Park, Yong-Gyu
Abstract : Abstract: This study aimed to examine average height loss and the relationship between height loss and socioeconomic status (SES) among the elderly in South Korea. Data were obtained from the Korean National Health and Nutrition Examination Survey 2008–2010. A total of 5265 subjects (2818 men and 2447 women) were included. Height loss was calculated as the difference between the subject's self-reported maximum adult height and their measured current height. The height loss values were divided into quartiles (Q1–Q4) for men and women. SES was determined using a self-reported questionnaire for education level, family income, and occupation. Height loss was associated with SES in all age groups, and mean height loss increased with age. In the relationship between education level and maximum height loss (Q4), men with ⩽6, 7–9, or 10–12 years of education had higher odds ratios for the prevalence of height loss (Q4) than men with the highest education level (≥13 years). With regard to the relationship between the income level and height loss (Q4), the subjects with the lowest income had an increased prevalence of maximum height loss (Q4) than the subjects with the highest income (odds ratios = 2.03 in men and 1.94 in women). Maximum height loss (Q4) was more prevalent in men and women with a low SES and less prevalent in men with a high SES than in men with a middle SES. Height loss (Q4) was associated with education level in men and with income level (especially low income) in men and women. Height loss was also associated with a low SES in men and women.